Neonatal dengue as never before - A case series - Alimelu Madireddi (Wolters Kluwer Medknow Publications, 2021)
Dengue is a Flavivirus, affecting about 100 million people annually and mainly in the tropical and subtropical countries. Neonatal dengue is uncommon and usually by vertical transmission or, in the postnatal period, by horizontal transmission. We describe the clinical profile, management and outcome of neonates with dengue infection. Ten patients were prospectively recruited from August to November 2019 during dengue epidemic season at Niloufer Hospital, Hyderabad, India. Four babies had vertical mode of transmission while 6 had horizontal mode of transmission. All babies were positive for Ns1 antigen and IgM dengue serology, confirming dengue infection. Fever, flushing and thrombocytopenia were observed in all the babies while 2 babies had hypotension requiring inotropes. Oxygen supplementation was required in 8 babies. There was no recorded mortality. We conclude that neonatal dengue should be considered as a differential diagnosis in a neonate with sepsis and thrombocytopenia especially in endemic regions. Judicious use of fluids (avoid excessive) and inotropes (dopamine) form the cornerstone of dengue management in neonates.